CLIMATE CHANGE AND FOOD CROP PRODUCTION IN IMO STATE NIGERIA: AN ANALYSIS OF 30 YEAR PERIOD - Okorie, Fidelis Chinazor; Njoku, John Didacus; Onweremadu, Emmanuel Uzoma; Iwuji, Martin Chidinma (African Journal of Social and Behavioural Sciences, 2019)
The study was conducted in Imo State in South-eastern Nigeria where rain fed agriculture is widely practiced. People in the area are affected by the current global food security crisis due to their total dependence on rainfall for agricultural production. It assesses relationships existing between climate change and food crop production in the area. Rainfall variability was used as climatic indicator and 30 yrs rainfall data were analysed using time-series line graphs model. Interviews were conducted and questionnaire was also administered to farmers in the area with the intension of ascertaining their perception of effects of climate change on their crops. Pearson.s Moment Coefficient of correlation was used in the Statistical analysis. The results show that (1) rainfall fluctuated moderately in the area with downward rainfall trends; (2) rainfall shift accounts for 0.03 percent variations in Cassava production and 1.19 percent variation in production of maize respectively in the last two (2) decades in the study area. That makes the correlation of rainfall with cassava and maize productions in the study area a very poor/weak one and a low one respectively. However, some other factors other than rainfall variability also, contributed to cause variations in the productive levels (decrease in production) particularly the arable crops in the state. Nonetheless, rainfall variability in Imo state is partially, responsible for the high variations recorded in the productivity and productivity efficiency for the major food crops under investigation. Recommendations were made to ensure increased productivity and sustainability for food security in the state.